2015
DOI: 10.1002/jcp.24928
|View full text |Cite
|
Sign up to set email alerts
|

Activation Of Nfatc2 in osteoblasts causes osteopenia

Abstract: Nuclear factor of activated T-cells (Nfat)c1 to c4 are transcription factors that play an undisputable role in osteoclastogenesis. However, Nfat function in osteoblastic cells is controversial. Constitutive activation of Nfatc1 and c2 in osteoblasts suppresses cell function, although the study of Nfat in vivo has yielded conflicting results. To establish the consequences of Nfatc2 activation in osteoblasts, we generated transgenic mice where a 3.6 kilobase fragment of the collagen type I α1 promoter directs ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…This potential discrepancy may be due to variability in the cellular composition of entheses (49), resulting in site-specific roles for NFATc2. In addition, recent studies also showed NFATc2 can directly inhibit osteoblast function and osteogenesis (50, 51), consistent with our finding.…”
Section: Discussionsupporting
confidence: 93%
“…This potential discrepancy may be due to variability in the cellular composition of entheses (49), resulting in site-specific roles for NFATc2. In addition, recent studies also showed NFATc2 can directly inhibit osteoblast function and osteogenesis (50, 51), consistent with our finding.…”
Section: Discussionsupporting
confidence: 93%
“…Importantly, the phenotype of 1-month-old mice revealed a lack of a bone-forming response to enhanced bone resorption, possibly invoking a direct or indirect inhibition of this process under conditions of Notch2 activation. In this context, we have found that Notch2 induces Nfatc2 in skeletal cells, and Nfatc2 suppresses osteoblast differentiation and function and may contribute to the uncoupling of a bone-forming response to the increase in bone resorption (70,71). 3 Histomorphometric analysis of cortical bone confirmed an increase in osteoclast number and bone resorption in the endocortical surface of 1-month-old Notch2 Q2319X mutants.…”
Section: Discussionmentioning
confidence: 81%
“…129 Moreover, thapsigargin stimu-lation of LS8 cells resulted in activation of NFAT (R.L., unpublished data), a family of transcription factors regulated by Ca 2+ signals. 130 As NFAT plays an emerging role in bone formation and bone remodeling, 131,132 SOCE-mediated NFAT activity in enamel cells may become an important are of study.…”
Section: Soce In Ameloblast Signaling and Developmentmentioning
confidence: 99%